2017
DOI: 10.1021/acs.orglett.7b03022
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Asymmetric Borylallylation of Vinyl Arenes

Abstract: A copper-catalyzed, enantioselective method for the borylallylation of vinyl arenes is reported. The reaction produces enantioenriched and functionalized organoboron compounds by sequentially incorporating boryl and allyl groups onto the C═C bond of vinyl arenes. Copper-catalyzed borylative coupling of vinyl arenes with allyl phosphates successfully proceeds in a regio- and enantioselective manner in the absence of a palladium cocatalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…improved this reaction and extended the alkene substrate to styrenes. High ee values and yields were usually obtained under these reaction conditions . Very recently, Hoveyda et al.…”
Section: Copper Catalysismentioning
confidence: 87%
“…improved this reaction and extended the alkene substrate to styrenes. High ee values and yields were usually obtained under these reaction conditions . Very recently, Hoveyda et al.…”
Section: Copper Catalysismentioning
confidence: 87%
“…1). [13] Although only three examples of alkene benzylboration were disclosed with styrene, a vinyl boronate, and a vinyl silane, this work nevertheless demonstrated the viability of a fully intermolecular 1,2-carboboration, setting the stage for further development to unlock the full potential of this transformation in organic synthesis.…”
Section: Three-component Alkene Carboboration Reactionsmentioning
confidence: 89%
“…From our earlier report on the borylative coupling of vinyl arenes with primary allylic electrophiles, we found that the use of allyl phosphates and N , N ‐dimethylacetylamide (DMA) solvent were crucial for good yield of product in the presence of a catalytic amount of CuCl and a chiral bisphosphine ligand. However, application of the previous reaction conditions to secondary allylic phosphate ( rac ‐ 2 a ) resulted in moderate yield and enantioselectivity despite promising E / Z selectivity.…”
Section: Methodsmentioning
confidence: 99%
“…[8,9] In particular,f ew examples of allylic substitutions of chiral alkylcopper speciesw ere reported with simple allyl electrophiles in respective reports by other groups [10] and our group (Scheme1a). [11] Although these methods were highly efficient, the reactions accommodated only simple allyl electrophiles, and the reaction with ar acemic secondary allylic electrophile resulted in am ixture of E/Z stereoisomers. [11a] Controlling E/Z selectivity in the copper-catalyzed allylic substitutionh as been an important issue as it creates an additional stereocomponenta nd, thus, stereochemically well-defined prochiral allylic electrophileso rc yclic electrophiles had to be used for high stereocontrol.…”
mentioning
confidence: 99%